99mTc-radiolabeled TPGS nanomicelles outperform 99mTc-sestamibi as breast cancer imaging agent - Tesan, Fiorella C. (2019)
Fil: Tesan, Fiorella C. Universidad de Buenos Aires. Facultad de Farmacia y Bioquímica; Argentina